2014
DOI: 10.3168/jds.2013-7600
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of caffeic acid against inflammation injury of primary bovine mammary epithelial cells induced by lipopolysaccharide

Abstract: Caffeic acid possesses multiple biological effects, such as antibacterial, antioxidant, antiinflammatory, and anticancer growth; however, what effects it has on bovine mastitis have not been investigated. The aim of this study was to verify the antiinflammatory properties of caffeic acid on the inflammatory response of primary bovine mammary epithelial cells (bMEC) induced by lipopolysaccharide (LPS), and to clarify the possible underlying mechanism. Bovine mammary epithelial cells were treated with various co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 47 publications
7
51
0
Order By: Relevance
“…The interaction between LPS and TLR4 results in the activation of intracellular signaling through myeloid differentiation factor 88 (MyD88) and TIR-domain-containing adapter-inducing interferon-β (TRIF) pathways, leading to the activation of major mitogen-activated protein kinases (MAPKs) and translocation of nuclear transcription factor-κB (NF-κB) (Sheldon and Roberts, 2010;Kawai and Akira, 2011;Huang et al, 2016). NF-κB regulates the expression of cytokines, including interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor-α (TNF-α), which are essential mediators of the inflammation response (Wang et al, 2012;Liu et al, 2014;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between LPS and TLR4 results in the activation of intracellular signaling through myeloid differentiation factor 88 (MyD88) and TIR-domain-containing adapter-inducing interferon-β (TRIF) pathways, leading to the activation of major mitogen-activated protein kinases (MAPKs) and translocation of nuclear transcription factor-κB (NF-κB) (Sheldon and Roberts, 2010;Kawai and Akira, 2011;Huang et al, 2016). NF-κB regulates the expression of cytokines, including interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor-α (TNF-α), which are essential mediators of the inflammation response (Wang et al, 2012;Liu et al, 2014;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2A). This was consistent with previous reports (Wellnitz and Kerr, 2004;Liu et al, 2014). In this study, LPS-induced inflammation injury of BMEC was assessed ( Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Apoptosis is involved in multiple organ dysfunction during septic shock (Hotchkiss et al, 1999). LPS has been shown to induce apoptosis in multiple cell types, such as macrophages and BMECs (Xaus et al, 2000;Liu et al, 2014). Current data showed that LPS stimulation demonstrated time and dosedependent effects on the viability of BMECs ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Cells were treated with LPS at concentrations of 0, 1, and 25 µg/ml for various time points depending on each experimental settings. LPS concentrations were chosen based on previous studies by others using mammary epithelial cells [18,20]. In the experiments for testing the effects of pharmacological inhibitors, cells were pretreated with the inhibitors (PD98059, LY294002, and SB203580) at 20 and 40 µM for 1 h, followed by stimulation with LPS at 0, 1, and 25 µg/ml for 12 h.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…These LPS concentrations were also chosen by others when treating mammary epithelial cells, owing to the capability of cell challenging without significant cell death [18,20].…”
Section: Cytotoxicity Of Phytoncide In Mac-t Cellsmentioning
confidence: 99%